2009
DOI: 10.1016/j.neuroscience.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The supplementary motor area contributes to the timing of the anticipatory postural adjustment during step initiation in participants with and without Parkinson's disease

Abstract: The supplementary motor area is thought to contribute to the generation of anticipatory postural adjustments (which act to stabilize supporting body segments prior to movement), but its precise role remains unclear. In addition, participants with Parkinson’s disease (PD) exhibit impaired function of the supplementary motor area as well as decreased amplitudes and altered timing of the anticipatory postural adjustment during step initiation, but the contribution of the supplementary motor area to these impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(222 citation statements)
references
References 61 publications
11
200
0
11
Order By: Relevance
“…The specific role of the vermis could be to provide the adaptive plasticity necessary to modify anticipatory adjustments for the full range of motor outputs. This speculation is supported by the finding that lesions of the cortical motor areas disrupt anticipatory postural adjustments (30), and cerebellar lesions abolish their plasticity (31).…”
Section: Discussionmentioning
confidence: 86%
“…The specific role of the vermis could be to provide the adaptive plasticity necessary to modify anticipatory adjustments for the full range of motor outputs. This speculation is supported by the finding that lesions of the cortical motor areas disrupt anticipatory postural adjustments (30), and cerebellar lesions abolish their plasticity (31).…”
Section: Discussionmentioning
confidence: 86%
“…5,11 ). The SMA contributes to the anticipatory postural adjustment for step initiation, which is impaired in PD patients 39 . In the higher primates and in particular those with bipedal gait, SMA/PM (premotor area) projections to the pedunculopontine nucleus (PPN), in addition to the pontomedullary reticular formation, may play a crucial role of initiation of locomotion with appropriate postural control.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it appears that the duration of APA in the reactiontime condition was precisely tuned by the central nervous system to reach the minimal possible value allowing complete adaptation, thus revealing a possible functional link between the programming of APA amplitude and APA duration. Interestingly, Jacobs et al (2009) suggested that the supplementary motor area may contribute to the timing of APA associated with step initiation, whereas APA amplitude may be relegated to the primary motor cortex or basal ganglia. The present results illustrate how these neural structures may work together to ensure optimal motor performance and postural stability.…”
Section: Influence Of Temporal Pressure On Motor Performancementioning
confidence: 99%